Promoting and sharing knowledge among researchers through USBET / Nor Azizah Talkis - Talkis, Nor Azizah (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
The 3rd Undergraduate Seminar of Built Environment and Technology (3rd USBET) was held on May 15, 2018 by the Faculty of Architecture, Planning and Surveying (FSPU) and successfully led by the Project Coor-dinator, Dr Lilawati Ab Wahab. This year's USBET, in continuation of the previous USBET debuted in 2016, has seen an increase in participation for both oral and poster presentation, with 35 and 65 presenters respective-ly, amounting to an overall of 100 presenters from five local universities.